Individuals with chronic pain have the same response to placebo analgesia as healthy controls in terms of magnitude and reproducibility. Issue 12 (December 2020) - Power, Andrea; Brown, Christopher Andrew; Sivan, Manoj; Lenton, Ann; Rainey, Timothy; El-Deredy, Wael; Jones, Anthony Kenneth Peter; Watson, Alison
Abstract : Abstract: It is unclear whether a diagnosis of chronic pain is associated with an increase or decrease in the placebo response. The aim of this study was to use an experimental placebo conditioning paradigm to test whether expectancy for pain relief impacts on acute pain perception in individuals with a chronic pain diagnosis of osteoarthritis (OA) or fibromyalgia (FM), compared to healthy individuals (HIs). An inert cream was applied to the dominant forearm of participants (60 OA, 79 FM, and 98 HI), randomly assigned to either a placebo or control group. In both groups, an inactive cream was applied to the dominant forearm. The placebo group was told this may or may not be a local anaesthetic cream, whereas the control group was told the cream was inactive. Laser pain was delivered, and numerical pain intensity ratings collected before, during, and after cream application, along with expectation of pain relief and anxiety. The procedure was repeated 2 weeks later to assess reproducibility. There was a significant reduction in pain in the placebo group, independent of clinical diagnosis. Diagnostic groups (OA, FM, and HI) did not differ in their magnitude of placebo analgesia or expectancy of pain relief. The results were similar in the repeat session. The results demonstrate that individuals with chronic pain respond to experimental placebo analgesia in a similar and reproducible manner as HIs, despite higher levels of psychological comorbidity. This has implications for using placebo analgesia in the treatment of chronic pain. Abstract : Supplemental Digital Content is Available in the Text.We found equivalent and reproducible changes in expectancy, anxiety, and pain experience as a result of an experimental placebo procedure in individuals with OA and FM compared to pain-free healthy volunteers. The placebo effect did not seem to be predicted by or mediated by expectation or anxiety. Treatment approaches seeking to maximise placebo analgesia may have equal chance of success in both OA and FM populations.